Design optimization for an additively manufactured automotive component - Abdi, Meisam; Ashcroft, Ian; Wildman, Ricky D. (Inderscience, 2018)
The aim of this paper is to investigate the design optimization and additive manufacture of automotive components. A Titanium brake pedal processed through Selective Laser Melting (SLM) is considered as a test case. Different design optimisation techniques have been employed including topology optimization and lattice structure design. Rather than using a conventional topology optimization method, a recently developed topology optimization method called Iso-XFEM is used in this work. This method is capable of generating high resolution topology optimised solutions using isolines/isosurfaces of a structural performance criterion and eXtended Finite Element Method (XFEM). Lattice structure design is the other technique used in this work for the design of the brake pedal. The idea is to increase the stability of the brake pedal to random loads applied to the foot pad area of the pedal. The use of lattice structures can also significantly reduce the high residual stress induced during the SLM process. The results suggest that the integration of the design optimization techniques with a metal additive manufacturing process enables development of a promising tool for producing lightweight energy efficient automotive components.